Histological Study of Skin in Adult Black Bengal Goat - Kumar, Manish; Tudu, Nirmal Kumar; Mandal, Kumar; Das, Partha; Gautam, Avnish Kumar; Ray, Nayanika (Indian Journal of Veterinary Anatomy, 2023)
To undertake the present investigations, fresh skin samples of seven adult Black Bengal goats were taken from healthy animals irrespective of sex from local slaughter house ofKolkata. The skin samples from different body regions, neck region (dorsal, lateral and ventral), thorax region (dorsal, lateral and ventral), abdomen region (dorsal, lateral and ventral) and thigh region of body of seven Black Bengal goats were collected immediately after slaughtering in ice box. Histologically, the skin of all body region of Black Bengal goat consisted of two layers, the epidermis layer followed by dermis layer. The skin epidermis of the Black Bengal goat was composed ofkeratinized stratified epithelium which consisted of five layers viz., stratum basale, stratum spinosum, stratum granulosum, stratum lucidum and stratum comeum. Beneath the epidermis, the dermis layer was observed in which the hair follicles, sweat glands, sebaceous glands, arrector pilli muscles and blood vessels were present. The dermis layer consisted of dense connective tissue and was divisible into superficial papillary layer and deep reticular layer.